Tempo, experiência e trabalho docente: crítica da atividade do professor no Ensino Fundamental - Martinez, Domenica (2014)
This research, of the exploratory kind, has as a study object the time and the experience of the teachers of the Primary. Considering there are historical evidences regarding changes of the meanings of time in the contemporary society and that the teaching work, eventhough, as all work done in the administered society, is determined by the means of the material production and social conventions, the objectives of the study are: analyze the objectivication of time related to the formation and to the teaching work through the identification of working tools and the pedagogical practices that promote them by pointing, specially, the expressions that manifest the destinies of the vital pulses and the language, means that actualize the accomplishment of the experience and rely on reflection, that by itself requires time. To achieve the objectives, it was used as empirical data a sample of 14 master and doctorate researches, chosen from the Banco de Teses do Coordenação de Aperfeiçoamento de Pessoal de Nível Superior CAPES, that had as a study object the time of the teaching work of the Primary; the chosen sample has investigations defended between 1997 and 2011. The results point out the impossibilities of the teacher's formation experience both on the objective determinations of the school about controlling the working time of the professional, and it's attitudes. In the same way, it is identified on the chosen researches tendencies of interventions on the time of the teaching work in the view of adapting and situating it and inculcating in the teacher a subjective appropriation of time, so that the control over him, done until then done explicitly through clocks and calendars,, tended to be replaced by self control, mainly with the justifications of doing services aimed at the community through technological means. Eventhough the justifications that sustain those interventions manifest appropriations of the progressive ideals advocated by bourgeois revolutions, it is observed what is effected by it through the spreading of the ideology of the technological rationality, by doing the use of the reflexive intelligence as the basis of the intellectual work on which the teacher is inserted to, an instrument of domination that tends do abnegate the social contradictions. The theoretical referential that gives ground to this research is the Critical Theory, specially the elaborations of Max Horkheimer, Theodor Wiesengrund-Adorno, Herbert Marcuse and Walter Benjamin, highlighting the concepts of society, work, experience and ideology of the technological ideology. It is also called upon other philosophers to elaborate the research such as Karl Marx, Friedrich Engels, Sigmund Freud and George Herbert Mead